Plasmon-enhanced reverse water gas shift reaction over oxide supported Au catalysts. Issue 5 (2nd December 2014) - Upadhye, Aniruddha A.; Ro, Insoo; Zeng, Xu; Kim, Hyung Ju; Tejedor, Isabel; Anderson, Marc A.; Dumesic, James A.; Huber, George W.
Abstract : Visible light driven plasmon-enhanced reverse water gas shift reaction over Au/TiO2 catalysts for CO2 conversion. Abstract : We show that localized surface plasmon resonance (LSPR) can enhance the catalytic activities of different oxide-supported Au catalysts for the reverse water gas shift (RWGS) reaction. Oxide-supported Au catalysts showed 30 to 1300% higher activity for RWGS under visible light compared to dark conditions. Au/TiO2 catalyst prepared by the deposition–precipitation (DP) method with 3.5 nm average Au particle size showed the highest activity for the RWGS reaction. Visible light is converted into chemical energy for this reaction with up to a 5% overall efficiency. A shift in the apparent activation energy (from 47 kJ mol −1 in dark to 35 kJ mol −1 in light) and apparent reaction order with respect to CO2 (from 0.5 in dark to 1.0 in light) occurs due to the LSPR. Our kinetic results indicate that the LSPR increases the rate of either the hydroxyl hydrogenation or carboxyl decomposition more than any other steps in the reaction network.